Students readiness in learning MAT037 using Online Distance Learning (ODL) / Azlina Mohd Mydin ... [et al.] - Mohd Mydin, Azlina Mohd Mydin; Wan Mohammad, Wan Anisha; Johan, Elly Johana; Kadar, Rozita (Unit Penerbitan JSKM, UiTM Pulau Pinang, 2021)
Pre-Commerce is one of a programme in Pre -HigherEducation Program (PPT), in UiTM. This program is offered to students who do not get any offer from IPTA but they have a high spirit to continue their studies to a higher levels. This research is purposely to dicuss how the lecturers conducting the MAT037 course during the online classe. In this study also we will elobrate the teaching medium used by the lecturer for teaching the mathematic course. An online survey has been conducted to study the student readiness for online classe so that the lecturer are able to conduct the classes as suitable with student requirement . The Pre-Commerce student exspecially from UiTM Cawangan Pulau Pinang are the sample of this study.